Reduced Cannabinoid CB(1) Receptor Binding in Alcohol Dependence Measured with Positron Emission Tomographys - Hirvonen, Jussi (2012)
Brain cannabinoid CB(1) receptors contribute to alcohol-related behaviors in experimental animals, but their potential role in humans with alcohol dependence is poorly understood. We measured CB(1) receptors in alcohol dependent patients in early and protracted abstinence, and in comparison with control subjects without alcohol use disorders, using positron emission tomography (PET) and [(18)F]FMPEP-d(2), a radioligand for CB(1) receptors. We scanned 18 male inpatients with alcohol dependence twice, within 3–7 days of admission from ongoing drinking, and after 2–4 weeks of supervised abstinence. Imaging data were compared with those from 19 age-matched healthy male control subjects. Data were also analyzed for potential influence of a common functional variation (rs2023239) in the CB(1) receptor gene (CNR1) that may moderate CB(1) receptor density. On the first scan, CB(1) receptor binding was 20–30% lower in patients with alcohol dependence than in control subjects in all brain regions and was negatively correlated with years of alcohol abuse. After 2–4 weeks of abstinence, CB(1) receptor binding remained similarly reduced in these patients. Irrespective of diagnostic status, C allele carriers at rs2023239 had higher CB(1) receptor binding compared to non-carriers. Alcohol dependence is associated with a widespread reduction of cannabinoid CB(1) receptor binding in the human brain and this reduction persists at least 2–4 weeks into abstinence. The correlation of reduced binding with years of alcohol abuse suggests an involvement of CB(1) receptors in alcohol dependence in humans.